Approach to improve the quality of movie and television series filming locations in Thailand to promote tourism: แนวทางการยกระดับคุณภาพของสถานที่ถ่ายทำภาพยนตร์และละครโทรทัศน์ในประเทศไทยเพื่อส่งเสริมการท่องเที่ยว - Ngamsilstian, Atithep (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2020)
This article is intended to 1) Study situations, models, needs and trends of movie and television series filming locations in Thailand to promote tourism. 2) Propose an approach to improve the quality of movie and television series filming locations in Thailand to promote tourism. Data collection was conducted using in-depth interviews with key informants, both government and private sector representatives and content analysis. Study results: the government sector found that Thailand has a very high potential for being a shooting location for movies and TV series because of many beautiful locations. The government had integrated marketing ingredients in every aspect to create a quality image. There was a policy to stimulate tourism trend in order to increase income from the property of the land. The private sector found that Influence of movies and TV series quality that could create a nation. The production camp would be built according to the audience's flow by doing everything by themselves. An approach to improve the quality of movie and television series filming locations in Thailand to promote tourism, the government and private sectors should collaborate in integrating development of film and TV series industry. Importantly, the government should provide full support to the private sectors, such as providing the source of funding, increasing the publicity of beautiful locations in Thailand through movies and TV series to promote tourist spots to be well-known both at home and abroad, focusing on developing many provinces as film-shooting destinations, facilitating coordination with one stop service, increasing incentive to be better than competitors. The private sector should develop script writing and filming to be effective in order to encourage films and TV series shooting in Thailand to support better quality and more successful travel.